Effect of tanshinone II on cell growth of breast cancer cell line type MCF-7 and MD-MB-231 - Nicolin, Vanessa; Fancellu, Giovanni; Valentini, Roberto (Italian Journal of Anatomy and Embryology, 2014)
Breast cancer is the most common form of cancer in women and the leading cause of cancer death in American women, with over 207,090 new cases of invasive breast cancer in women and about 39,840 deaths from breast cancer in 2010. Current therapies for breast cancer usually have variable effectiveness with high toxicity to normal tissues, and breast tumours often develop metastasis and drug resistance. Therefore, searching for effective regimens with minimal side effects remains the top priority in breast cancer research. The objectives of this study were to evaluate the effects of tanshinone II from a Chinese herb, Salvia miltiorrhiza, on the growth of breast cancer cells type MCF-7 and MDA-MB-231.